Stereoselective Synthesis of Cyclohexane Derivatives: Tandem Lithium Iodide Mediated Intramolecular Conjugate Addition of Thiols to α,β-Bisenones - Jeon, Minseok; Yun, Chaeyoung; Seo, SungYong (Synthesis, 2022)
A tandem intramolecular conjugate addition reaction was conducted with α,β-bisenones as selected Michael acceptors which were converted into 1,2,3-trisubstituted six-membered rings in the presence of activated sulfur nucleophiles. The products were obtained in good to excellent yields (maximum yield: 99%). Various substituted α,β-bisenones and sulfur nucleophiles were examined to understand the substrate scope of the reaction. Only one diastereomer was isolated, as lithium iodide mediated enolate trapping reactions improve the stereoselectivity of reactions involving 1,2,3-trisubstituted cyclohexanes.
Keywords: stereoselectivity; tandem conjugate addition; lithium iodide; α,β-bisenones; thiols